Physics Online Learning during the Covid-19 Pandemic uses a Guided Inquiry Model with Experimental Methods on teamwork Ability and Student Learning Outcomes - Ilvi Maulida Nurdiana; Widha Sunarno; Daru Wahyuningsih (Postgraduate, University of Mataram, 2021)
This study aims to determine the level of teamwork in online learning using a guided inquiry model with experimental methods, and the effectiveness of a guided inquiry learning model with experimental methods in online learning on student cognitive learning outcomes. The material used is dynamic fluid. The type of this study was a quasi-experiment with a research design is one group pretest-posttest design. This research was conducted at SMAN 2 Tanggul Jember in October 2020. The research sample used was 36 students of class XI MIPA 1. Data collection techniques are using tests and non-tests. Teamwork data collection techniques use a questionnaire given to students after learning via a google form, while the data on the effectiveness of the guided inquiry model was seen from the students' cognitive learning outcomes obtained from the pre-test and post-test scores. Teamwork data analysis techniques use Microsoft Excel to determine the description of data analysis, while the learning effectiveness data were analyzed using the N-gain test. The results of the data analysis showed that the level of teamwork ability after online learning was carried out using the guided inquiry model with the experimental method was mostly classified as medium and the guided inquiry learning model with the experimental method which is effectively used in online learning on student cognitive learning outcomes with an N-gain score of 0.514